Mother of God : a history of the Virgin Mary - Rubin, Miri, 1956- (New Haven : Yale University Press, 2009)
"Mary, the mother of Jesus, is one of the most powerful, influential and complex of all religious figures. The inspiration of faith, a model for women, the subject of innumerable paintings, sculptures, pieces of music and churches, Mary is so entangled in our world that it is impossible to conceive of the history of Western culture and religion without her." "Miri Rubin's Mother of God is a major work of cultural imagination. Mary's role in the Gospels itself is a relatively minor one, and yet in the centuries during which Christianity established itself she emerged as a powerful, strange and ungovernable force, endlessly remade and reimagined by wave after wave of devotees, ultimately becoming 'a sort of God', in ways that have made some Christians uneasy" "Whether talking about the vast public festivals celebrating Mary that sweep up entire communities or the intense private agony of individual devotion, Rubin's book is a triumph of sympathy and intelligence. Throughout Christianity's journey from mysterious origins to global religion, Mary has been a profound presence in countless lives - Mother of God is the story of that presence and a book that raises profound questions about the human experience."--BOOK JACKET.
From temple maiden to the bearer of God: to the year 431 -- The earliest glimpses of Mary -- Mary in a Christian empire -- Versions of Mary -- Mary of the imperial state -- From the Eastern Mediterranean to the Irish Sea: to the year 1000 -- Mary of the Christian empire -- Beyond the Greek world -- The emergence of European Mary -- The emergence of Mary's hegemony: 1000-1200 -- Mary of the cloister -- Mary of polemic and encounter -- Abundance and ubiquity -- Mary, local and familiar: 1200-1400 -- Mary in liturgy, song, and prayer -- Mary, the friars, and the mother tongue -- Teaching Mary in parish and home -- Mary's miracles as reward and as punishment -- Mary at the foot of the cross -- Mary and women, Mary and men -- Mary as queen and reformer: 1400-1500 -- Mary the sublime -- Mary: unlike any other -- Mary of parish practice and family life -- Mary: a world of devotional possibilities -- Mary reformed, Mary global: 1500 and beyond -- Mary of reform and reformation -- From Europe to the rest of the world -- Mary in a world of neighbouring diversity -- After Mary: a conclusion.
Includes bibliographical references (p. 425-509) and index.
Keywords: Mary, -- Blessed Virgin, Saint -- History of doctrines; Mary, -- Blessed Virgin, Saint -- Devotion to -- History; Mary, -- Blessed Virgin, Saint -- Art